Cassava physiology program review, 1972 - Cock, James H. (International Center for Tropical Agriculture, 1972)
Initial research on the physiology of the cassava plant will study the growth cycle of a heavy-and a medium-branched var. The effect of LAI, N and planting density will be determined as well. Other expt will study plant response to N, mineral requirements, induction of flowering, planting dates and the development of rapid propagation systems. (CIAT)